2017
DOI: 10.1111/zph.12359
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Brucella spp. in feral swine (Sus scrofa) at abattoirs in Texas, USA

Abstract: Various tissues, nasal swabs, urine and blood samples were collected from 376 feral swine at two federally inspected abattoirs in Texas during six separate sampling periods in 2015. Samples were tested for Brucella spp. by culture and serology. Brucella spp. were cultured from 13.0% of feral swine, and antibodies were detected in 9.8%. Only 32.7% of culture-positive feral swine were also antibody positive, and 43.2% of antibody-positive feral swine were culture positive. Approximately, the same number of males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 25 publications
4
25
0
Order By: Relevance
“…Additionally, wild pigs carry numerous diseases, with meat processed in commercial plants in Texas having been found positive for multiple disease pathogens, including influenza A, Leptospira , Trichinella , Toxoplasma , and Brucella spp. [ 12 , 13 ]. These authors indicated 48.9% of tested pigs were positive for antibodies of one or more serovars of Leptospira spp.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, wild pigs carry numerous diseases, with meat processed in commercial plants in Texas having been found positive for multiple disease pathogens, including influenza A, Leptospira , Trichinella , Toxoplasma , and Brucella spp. [ 12 , 13 ]. These authors indicated 48.9% of tested pigs were positive for antibodies of one or more serovars of Leptospira spp.…”
Section: Introductionmentioning
confidence: 99%
“…This side‐by‐side testing found that only 52% of sera from culture positive animals were antibody positive, indicating that feral swine are carriers of B. suis and that serological results are a suboptimal indicator of infection. These findings were echoed by Pedersen, Bauer, et al () when evaluating B. suis isolation and antibody presence in feral swine in two abattoirs in Texas. The B. suis organism was detected in 13% of feral swine sampled, while only 9.8% of animals were seropositive, again demonstrating that serology underestimates the true prevalence of B. suis infection in feral swine.…”
Section: Resultsmentioning
confidence: 78%
“…Further work with feral swine in the United States identified B. suis culture‐positive animals as a result of routine culling activities (Pedersen et al., ) as well as in feral swine slaughter establishments (Pedersen, Bauer, et al., ). Apparently healthy animals from 16 counties in eight states were culled for collection and evaluation of lymph nodes and blood for bacteria and antibody presence, respectively (Pedersen et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations